REPRESENTASI KEKERASAN TERHADAP PEREMPUAN DALAM EKRANISASI NOVEL SEPERTI DENDAM, RINDU HARUS DIBAYAR TUNTAS - Febrianto, Diki; Tjahjandari, Lily (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
Violence against women through narratives and scenes becomes one of the interesting discussions, especially in the novel adapted into the film Seperti Dendam, Rindu Harus Dibayar Tuntas. This research aims to uncover the representation of violence against women in the adaptation process from novel to film. This research is qualitative with a descriptive method. The approach used in this research is to look at the narrative aspects of the novel, relationships, and correlations of violence against women. Violence against women in film uses the concepts of cinematography, vehicle transfer, and narrative, in building visuals of violence against women. The results of this study show the representation of violence against women through Iteung and Rona Merah. Iteung shows the relationship between her childhood and the formation of masculine character in adolescence. This also shows the ecranisation in the form of reduction in the film. Rona Merah provides an image as an object of sexual violence who experiences psychological disorders as a form of trauma in the past. New media other than film are the caricatures on the tailgate of a truck, which are closely related to the problems of men and women.